Two decades of research on early career faculties (ECFs): A bibliometric analysis of trends across regions - Yusop, Farrah Dina; Abdul Ghaffar, Fauza; Danaee, Mahmoud; Firdaus, Amira Sariyati; Hamzaid, Nur Azah; Abu Hassan, Zahiruddin Fitri; Senom, Fatiha; Ebrahim, Nader Ale; Bong, Yii Bonn; Yap, Min Chen (Universiti Putra Malaysia, 2020)
Early Career Faculties (ECFs) are an important demographic of university faculty population shaping the future of the institution and higher education, despite the challenges they face as new academics. Analysis of scholarly output on ECFs offers useful data to inform and aid both national policy formulations and institutional planning decisions especially in ECFs' support and development. Peer-reviewed high impact journals and academic databases provide highly valid and reliable sources of data and information on ECFs. This study examines the trend of ECFs research over two decades comparing scholarly output and research impact across global regions, in Web of Science and Scopus Elsevier. The bibliometric analysis highlights key topics of research and publications related to ECFs and identify the regions and countries most actively research on the topic. The trend of research on ECFs has been found to increase exponentially beginning the 1990s worldwide, mostly from western institutions (76%). Publications after the year 2012 focused more on issues related to ECFs' preparation towards life in academia, their motivation, and challenges, the support structure for ECFs and strategies to adapt to life as faculty members. Such bibliometric analysis findings can be a useful reference for policy formulation within national or regional systems of higher education, and institutional strategic planning. © 2020 Universiti Putra Malaysia Press.